The changes in family functioning and family happiness during the COVID-19 pandemic: The situation in Thailand - Limsuwan, Nida; Prachason, Thanavadee; Wisajun, Pattarabhorn (Frontiers in Public Health, 2022)
Background The effects of the COVID-19 pandemic on family well-being and functioning were generally a concern for healthcare providers in many countries. Objectives To explore the changes in family functioning and family happiness during the pandemic in Thailand and to investigate factors associated with the changes in family happiness. Methods This was a cross-sectional study conducted between November and December 2021. Online questionnaires regarding family functioning, family happiness, domestic violence, and COVID-19-related experiences were used. Results A total of 485 participants were included in this study. The perceived family happiness slightly decreased from 8.19 (pre-pandemic score) to 7.62 (post-pandemic score). In contrast, the general family functioning (SCORE-15 index), strength, and communication subscale scores after the onset of the COVID-19 pandemic were significantly lower than those of the pre-pandemic period. Moreover, the prevalence of verbal and physical violence significantly reduced during the pandemic. In addition, the change in family functioning was the strongest factor associated with the change in family happiness. Conclusion In general, family functioning slightly improved; however, perceived family happiness decreased during the pandemic. In addition, the change in family functioning was the strongest factor associated with the change in family happiness.